PATTERNS OF CLINICALLY SIGNIFICANT COGNITIVE IMPAIRMENT IN HOARDING DISORDER. Issue 3 (16th October 2015) - Mackin, R. Scott; Vigil, Ofilio; Insel, Philip; Kivowitz, Alana; Kupferman, Eve; Hough, Christina M.; Fekri, Shiva; Crothers, Ross; Bickford, David; Delucchi, Kevin L.; Mathews, Carol A.
Abstract : Objectives: The cognitive characteristics of individuals with hoarding disorder (HD) are not well understood. Existing studies are relatively few and somewhat inconsistent but suggest that individuals with HD may have specific dysfunction in the cognitive domains of categorization, speed of information processing, and decision making. However, there have been no studies evaluating the degree to which cognitive dysfunction in these domains reflects clinically significant cognitive impairment (CI). Methods: Participants included 78 individuals who met DSM‐V criteria for HD and 70 age‐ and education‐matched controls. Cognitive performance on measures of memory, attention, information processing speed, abstract reasoning, visuospatial processing, decision making, and categorization ability was evaluated for each participant. Rates of clinical impairment for each measure were compared, as were age‐ and education‐corrected raw scores for each cognitive test. Results: HD participants showed greater incidence of CI on measures of visual memory, visual detection, and visual categorization relative to controls. Raw‐score comparisons between groups showed similar results with HD participants showing lower raw‐score performance on each of these measures. In addition, in raw‐score comparisons HD participants also demonstrated relative strengths compared to control participants on measures of verbal and visual abstract reasoning. Conclusions: These results suggest that HD is associated with a pattern of clinically significant CI in some visually mediated neurocognitive processes including visual memory, visual detection, and visual categorization. Additionally, these results suggest HD individuals may also exhibit relative strengths, perhaps compensatory, in abstract reasoning in both verbal and visual domains.